A Risk-Based Approach to Financial Implications of Procurement Fraud in Public Health Facilities - Nsowah, Johnson; Anane, Augustine; Afoakwah, Emmanuel Ampong; Asare, Evelyn Nsiah; Adomako, Francis (International Review of Management and Marketing, 2026)
Procurement fraud significantly threatens healthcare delivery in developing economies, yet its financial impacts are underexplored This study examined procurement fraud in public health facilities across Ghana’s Bono Region, using the fraud triangle and fraud diamond theories A survey of 240 staff from procurement, finance, and management departments in eight districts revealed that 75 4% perceived procurement fraud as common, with inflated pricing (25 0%) and kickbacks (20 8%) most prevalent Analysis showed strong correlations between procurement fraud and financial losses (r = 0 872), rising operational costs (r = 0 928), and reduced service quality (r = 0 768) Every 1% increase in procurement fraud corresponded to a 4 2% rise in financial losses Contributing factors included weak internal controls, poor transparency, and external pressures The study recommends robust procurement procedures, clear duty segregation, and comprehensive fraud risk management to mitigate these impacts and improve financial performance in health sector.